Upholding Judicial Independence through the Practice of Judicial Activism in Constitutional Review: A Study by Constitutional Judges - Ardhanariswari, Riris; Nursetiawan, Eko; Amalia, Syarafina Dyah; Cahyani, Enny Dwi; Fadzil, Rozlinda Mohamed (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
The practice of judicial activism, though not formally defined within the jurisdiction of the Constitutional Court (MK), is implicitly recognized as an integral element of independent judicial power. The importance of this independence is underscored as a fundamental necessity for the preservation of law and justice. This research utilized a normative juridical methodology, incorporating conceptual, comparative, and case-based analysis. The study findings reveal that judicial activism, as practiced within the Constitutional Court, is underpinned by independent judicial authority. Moreover, this practice aligns with the tenets of progressive legal doctrines, which not only acknowledge the significance of codified legal provisions but also endorse legal innovations for the pursuit of justice. The practice of judicial activism within the Constitutional Court is indispensable for reinforcing the principle of checks and balances. The subjective and abstract nature of judicial activism, however, necessitates objective validation through the principle of virtue jurisprudence.